Evaluation Criteria and Indicators of Communicative Competence of Adolescents with Language Disorder - Ušča, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Communicative competence is called as one of the transversal composed competencies in European reference framework. The article focuses on adolescents with language disorder, the development of communicative competence and the evaluation of the problem. The development of communicative competence is burdened because of the underdeveloped language. This constitutes a menace to successful participation in further professional, cultural, political and social life. Communicative competence evaluation criteria and the indicators are posed. Certain correlations were found out in the processing of data with SPSS and AQUAD 6 programs.